1999
DOI: 10.1177/089686089901900605
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and Interstitial Changes in the Peritoneum of Capd Patients with Peritoneal Sclerosis

Abstract: Objective To analyze morphological changes in the peritoneum of peritoneal sclerosis (PS) patients. Emphasis was put on vascular abnormalities, because the continuous exposure to glucose-based dialysis solutions could cause diabetiform changes and because longitudinal transport studies suggested the development of a large peritoneal vascular surface area. Design Peritoneal biopsies from continuous ambulatory peritoneal dialysis (CAPD) patients were investigated in two studies. Diabetic patients were excluded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
188
1
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 300 publications
(201 citation statements)
references
References 40 publications
(53 reference statements)
8
188
1
4
Order By: Relevance
“…Peritoneal dialysis (PD) is an attractive treatment for patients with end-stage renal failure. Several lines of evidence have shown that long-term peritoneal dialysis is often accompanied by functional and histopathological alterations in the peritoneum [1][2][3][4]. The characteristic features of chronic peritoneal damage in peritoneal dialysis include decreased ultrafiltration capacity associated with submesothelial fibrosis, accumulation of extracellular matrix, and angiogenesis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Peritoneal dialysis (PD) is an attractive treatment for patients with end-stage renal failure. Several lines of evidence have shown that long-term peritoneal dialysis is often accompanied by functional and histopathological alterations in the peritoneum [1][2][3][4]. The characteristic features of chronic peritoneal damage in peritoneal dialysis include decreased ultrafiltration capacity associated with submesothelial fibrosis, accumulation of extracellular matrix, and angiogenesis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The development of ultrafiltration failure is an important problem in about one-third of PD patients treated for 4-6 years (32,33). It is associated with the development of a fast transport status (11,32,33), caused by peritoneal neoangiogenesis (12,(34)(35)(36), that can be induced by long-term exposure to glucose-containing dialysis solutions (37). In addition, this type of ultrafiltration failure is also characterized by impaired free water transport (33,(38)(39)(40).…”
Section: Acquired Fast Transportersmentioning
confidence: 99%
“…Simple, yet time consuming, studies of peritoneal membrane histology in peritoneal dialysis patients show strik-ing abnormalities that worsen over time. 4,5 These include loss of the mesothelial cell layer, progressive submesothelial fibrosis and proliferation of submesothelial blood vessels with an associated vasculopathy. These changes correlate with and are thought to account for the deterioration in peritoneal membrane dialysis and ultrafiltration functions.…”
Section: What Causes the Failure Of The Peritoneal Membrane And Is Imentioning
confidence: 99%